Effect of Carbon Black Nanoparticle on Neonatal Lymphoid Tissues Depending on the Gestational Period of Exposure in Mice - Onoda, Atsuto; Okamoto, Saki; Shimizu, Ryuhei; El-Sayed, Yasser S.; Watanabe, Shiho; Ogawa, Shuhei; Abe, Ryo; Kamimura, Masao; Soga, Kohei; Tachibana, Ken; Takeda, Ken; Umezawa, Masakazu (Frontiers in Toxicology, 2021)
Introduction: Particulate air pollution, containing nanoparticles, enhances the risk of pediatric allergic diseases that is potentially associated with disruption of neonatal immune system. Previous studies have revealed that maternal exposure to carbon black nanoparticles (CB-NP) disturbs the development of the lymphoid tissues in newborns. Interestingly, the CB-NP-induced immune profiles were observed to be different depending on the gestational period of exposure. It is important to identify the critical exposure period to prevent toxic effects of nanoparticles on the development of the immune system. Therefore, the present study was aimed to investigate the effect of CB-NP on the development of neonatal lymphoid tissues in mice, depending on the gestational period of exposure. Methods: Pregnant ICR mice were treated with a suspension of CB-NP (95 µg/kg body weight) by intranasal instillation; the suspension was administered twice during each gestational period as follows: the pre-implantation period (gestational days 4 and 5), organogenesis period (gestational days 8 and 9), and fetal developmental period (gestational days 15 and 16). The spleen and thymus were collected from offspring mice at 1, 3, and 5-days post-partum. Splenocyte and thymocyte phenotypes were examined by flow cytometry. Gene expression in the spleen was examined by quantitative reverse transcription-polymerase chain reaction. Results: The numbers of total splenocytes and splenic CD3−B220− phenotype (non-T/non-B lymphocytes) in offspring on postnatal day 5 were significantly increased after exposure to CB-NP during the organogenesis period compared with other gestational periods of exposure and control (no exposure). In contrast, expression levels of mRNA associated with chemotaxis and differentiation of immune cells in the spleen were not affected by CB-NP exposure during any gestational period. Conclusions: The organogenesis period was the most susceptible period to CB-NP exposure with respect to lymphoid tissue development. Moreover, the findings of the present and previous studies suggested that long-term exposure to CB-NP across multiple gestational periods including the organogenesis period, rather than acute exposure only organogenesis period, may more severely affect the development of the immune system.